Software tools to handle the layers in a specialized GIS analyzing greenhouse gas emissions - Lyubinsky, B. B.; Khmelovskyi, V. Yu.; Danylo, Olha (Видавництво Львівської політехніки, 2013)
This article presents an approach to the development of architecture of the module “Slicing the Layers of Greenhouse Gas Inventory” of the geographic information system. It provides rationale for using the module, describes its architecture and key functions, and determines software requirements.
Keywords: information system; software product; greenhouse gas emissions; algorithm; maps; module